2021
DOI: 10.1080/21655979.2021.1958558
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA NBR2 suppresses the progress of colorectal cancer in vitro and in vivo by regulating the polarization of TAM

Abstract: Colorectal cancer (CRC) threatens the health of patients with high mortality, which lacks sensitive biomarkers for diagnosis to improve total survival. The lncRNA NBR2 is reported to be downregulated in CRC and suppresses the proliferation of CRC cells. However, the underlying mechanisms remain unclear. The present study aimed to explore the regulatory function of the lncRNA NBR2 on tumor-associated macrophage (TAM) polarization and its consequent anti-tumor effect. Two CRC cell lines were used in this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Lai et al. ( 32 ) showed that the long non-coding RNA NBR2 suppressed the progression of colorectal cancer in vitro and in vivo by regulating the polarization of TAM. In this study, Me49-DC-Exos co-cultured with RAW264.7 cells in vitro increased the fraction of CD86 + CD206 − cells and mRNA levels of INOS and TNF-α, suggesting that Me49-DC-Exo contributes to M1 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Lai et al. ( 32 ) showed that the long non-coding RNA NBR2 suppressed the progression of colorectal cancer in vitro and in vivo by regulating the polarization of TAM. In this study, Me49-DC-Exos co-cultured with RAW264.7 cells in vitro increased the fraction of CD86 + CD206 − cells and mRNA levels of INOS and TNF-α, suggesting that Me49-DC-Exo contributes to M1 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…NFs, CAFs and GC cells (AGS and SGC-7901) at the logarithmic growth stage were taken, and a cell co-culture model was established in 24-well plates by using transwell chambers (Corning, 0.4 μm in diameter) [ 24 ]. Briefly, NFs or CAFs (1 × 10 5 ) were inoculated in the upper chamber, and GC cells were seeded in 24-well plates (below the chambers) at 5 × 10 5 /well.…”
Section: Methodsmentioning
confidence: 99%
“…CCK-8 (Beyotime, China) was used to detect cell proliferation [ 17 ]. The BC cell lines were plated into 96-well plates (6x10 3 cells/well), and incubated for 0, 24, 48 and 72 h. Then 10 μl of CCK-8 reagent (Beyotime) was added to the plate for another 2 h. The absorbance was recorded using a microplate reader (BioTek China) at 450 nm.…”
Section: Methodsmentioning
confidence: 99%